Metaphor and board writing matter: The mediating roles of psychological distance and immersion in video lectures - Shanshan, Shang; Chenhui, Du; Lijuan, Luo (Computers and education, 2022)
The present study investigated the inﬂuence of metaphor and board writing on students’ learning performance, continuance intention, and recommendation intention through the mediating effects of psychological distance and immersion. Four aspects of psychological distance—temporal, spatial, social, and hypothetical distance—and immersion are introduced to identify the mechanism. Through a two (with versus without metaphor) by two (with versus without board writing) between-subject experimental design, 193 participants were randomly assigned to one of four sets of video lectures on the gradient descent method, followed by an online questionnaire. Partial least squares structural equation modeling was employed to validate the research model. The results demonstrate that metaphor has a significant effect on all four aspects of psychological distance and immersion, while board writing has an impact only on hypothetical distance. Social distance mediates the relationship between metaphor and learning performance, recommendation intention, and continuance intention; hypothetical distance mediates the interplay between metaphor, board writing, and learning performance; and immersion mediates the link between metaphor and recommendation intention. •A 2 × 2 between-subject experiment is used to analyze this topic.•Metaphor and board-writing are effective tools in video lectures.•Social and hypothetical distances and immersion play mediation roles.•Null impacts exist for temporal distance and spatial distance.•Immersion is not so important in the simple video context.